2019
DOI: 10.3390/app9050905
|View full text |Cite
|
Sign up to set email alerts
|

Research on Control of Intelligent Vehicle Human-Simulated Steering System Based on HSIC

Abstract: The experienced drivers with good driving skills are used as objects of learning, and road steering test data of skilled drivers are collected in this article. First, a nonlinear fitting was made to the driving trajectory of skilled driver in order to achieve human-simulated control. The segmental polynomial expression was solved for two typical steering conditions of normal right-steering and U-turn, and the hp adaptive pseudo-spectral method was used to solve the connection problem of the vehicle segmental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…where Φ, φ, and C are continuous functions defined on interval. The detailed description of GPM can be found in [31][32][33][34][35]. In GPM, the original optimal control problem can be approximated as static nonlinear programming (NLP).…”
Section: Brief Introduction Of Gpmmentioning
confidence: 99%
See 1 more Smart Citation
“…where Φ, φ, and C are continuous functions defined on interval. The detailed description of GPM can be found in [31][32][33][34][35]. In GPM, the original optimal control problem can be approximated as static nonlinear programming (NLP).…”
Section: Brief Introduction Of Gpmmentioning
confidence: 99%
“…To date, there is no professional software that can handle periodic optimization problems in a unified framework. Therefore, we must apply existing and mature optimization software to deal with this problem.In recent years, direct methods, especially pseudo-spectral methods (PSM), have become increasingly popular in the preliminary design phase of the aerospace industry with the development of computers and the corresponding optimization software, GPOPS (Gauss Pseudo-spectral OPtimization Software), which is based on some effective nonlinear programming methods, such as SQP (Sequential Quadratic Programming) [31][32][33][34][35]. GPOPS has been successfully applied to many trajectory optimization problems.…”
mentioning
confidence: 99%
“…This is because insufficient samples collected in the real world cannot meet the training requirements of the deep neural networks. The Hilbert-Schmidt independence criterion (HSIC) is proposed for training deep neural networks, and current studies have reported the extensions [15,16]. These methods show that the HSIC is comparable to cross-entropy-based back-propagation methods on popular classification datasets.…”
Section: Related Workmentioning
confidence: 99%
“…This is the value of the minimum turning radius, it is determined based on the size of the vehicle and the maximum steering angle as formula below. Also, many studies on improving steering effectiveness have been conducted and introduced [7][8][9][10]. To determine the turning radius of the vehicle, various dynamic models were used as single-track, double-track,… [11][12][13][14].…”
Section: Literature Reviewmentioning
confidence: 99%